Education and Support for Fathers Improves Breastfeeding Rates: A Randomized Controlled Trial. (November 2013) - Maycock, Bruce; Binns, Colin W.; Dhaliwal, Satvinder; Tohotoa, Jenny; Hauck, Yvonne; Burns, Sharyn; Howat, Peter
Background: Studies have identified numerous factors affecting breastfeeding initiation and duration, including maternal education, mode of delivery, birth weight, socioeconomic status, and support of the infant's father. Objective: The objective was to investigate the effects of an antenatal education session and postnatal support targeted to fathers. Methods: The Fathers Infant Feeding Initiative (FIFI Study) is a randomized controlled trial to increase the initiation and duration of breastfeeding that was conducted in 8 public maternity hospitals in Perth, Western Australia. A total of 699 couples were randomized within hospitals to either intervention or control groups. The intervention consisted of a 2-hour antenatal education session and postnatal support provided to fathers. Results: The any breastfeeding rate for the intervention group was significantly greater at 6 weeks: 81.6% in the intervention group compared to 75.2% in the control group, odds ratio 1.46 (95% CI, 1.01-2.13). After adjustment for age and hospital, the odds ratio for any breastfeeding in the intervention group was 1.58 (1.06-2.35) and for socioeconomic status (SES), 1.56 (1.06-2.30). The infants of older fathers were more likely to be breastfed at 6 weeks compared to infants of younger fathers ( P < .01), and infants of fathers with high SES more likely than infants of fathers with low SES ( P = .013). Conclusion: Even a small increase in breastfeeding rates brings public health benefits. In this study, a minimal intervention was found to significantly increase any breastfeeding at 6 weeks: 81.6% in the intervention group compared to 75.2% in the control group.